2018
DOI: 10.1007/s13239-018-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumatic Tubing System Transport on Platelet Apheresis Units

Abstract: Platelet apheresis units are transfused into patients to mitigate or prevent bleeding. In a hospital, platelet apheresis units are transported from the transfusion service to the healthcare teams via two methods: a pneumatic tubing system (PTS) or ambulatory transport. Whether PTS transport affects the activity and utility of platelet apheresis units is unclear. We quantified the gravitational forces and transport time associated with PTS and ambulatory transport within our hospital. Washed platelets and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The values of some biomarkers differed significantly from the duration of platelet storage, as measurements were also performed after 3−4 days of storage. 23 Zilberman‐Rudenko et al 24 sent apheresis platelet concentrates from the blood bank to the intensive care unit within their hospital by PTS and ambulatory transport (courier) while measuring gravitational force and transit time. The transported concentrates were examined in the laboratory after centrifugation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of some biomarkers differed significantly from the duration of platelet storage, as measurements were also performed after 3−4 days of storage. 23 Zilberman‐Rudenko et al 24 sent apheresis platelet concentrates from the blood bank to the intensive care unit within their hospital by PTS and ambulatory transport (courier) while measuring gravitational force and transit time. The transported concentrates were examined in the laboratory after centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…Sandgren et al 22 reported the effects of transport on the quality of buffy coat platelet concentrates and figured out that it had no observed. 24 The method of centrifuging samples after transport for pelleting is controversial and was questioned the same year by Odense University Hospital in Denmark. Centrifugation had a significant effect on the quality of the platelets, so that measurements after transport and centrifugation cannot provide meaningful values about the quality by transport of the concentrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advancing level of medical development in Chongqing and the implementation of universal health insurance policies, clinical component blood transfusions have become increasingly prevalent ( 1 , 2 ). The clinical demand for apheresis platelets has increased accordingly ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%